IMPROVING THE PROCEDURE FOR DETERMINING THE AMOUNT POWER AT THE VIOLATION OF CALCULATED ACCOUNTING NO FAULT OF CONSUMER - , В. В. (Municipal economy of cities. Series: «Economy science», 2013)
The question on the order of determination of the actual amount of electricity used in the case of temporary violation current account through no fault of the consumer. The analysis of the existing order and the method of calculating the amount nedovrahovanoyi electricity.